A description of alkaline phosphatases from marine organisms - 田继远 贾鸿冰 于娟 (Chinese journal of oceanology and limnology, 2016)
Alkaline phosphatases（APs） are non-specifi c phosphohydrolases, and they are widely used in clinical diagnostics and biological studies. APs are widespread in nature and exhibit dif ferent structural formulations. Based on the diversity of biogenetic sources, APs exhibit temperature-propensity traits, and they are classifi ed as psychrophilic, mesophilic, and thermophilic. In this article, the characteristics of psychrophilic APs from marine organisms were described, accompanied by a simple description of APs from other organisms. This review will facilitate better utilization of marine APs in the biotechnology fi eld.